THE DISTINCTION LAW OF PROCEDURE OF CORRUPTION CASE AND THE GENERAL COURT IN INDONESIAN CRIMINAL JUSTICE SYSTEM - Sukmareni Sukmareni; Roni Efendi; Riki Zulfiko (JCH (Jurnal Cendekia Hukum), 2021)
The Corruption Crime Court which based on Article 5 of the corruption Court Law has the authority to examine, adjudicate and decide on the corruption crime cases, money laundering crimes that was initiated by corruption crime and criminal acts that are expressly stipulated in other laws that considered as corruption act. The existence of sovereignty possessed by the State gives rise to jurisdiction (the authority to judge) in regulating the needs of the state both internally and externally. As a sovereign country, Indonesia has jurisdiction in resolving internal and external problems. There are three questions of the research; 1) What is the procedural law of the General Court in the Indonesian criminal justice system? 2) What is the procedural law of the Corruption Crime Court in the Indonesian criminal justice system?, 3) What is the difference between the procedural law of the Corruption Crime Court compared to the law of the General Court in the Indonesian criminal justice system ?.This research is hoped that the procedural laws used in the General Courts and the Corruption Crime Courts will be known, as well as the differences in the procedural laws used in the two Courts. This research is descriptive, using a normative juridical approach, especially the legal approach, used are secondary data as the main legal material in the form of laws relating to the procedural law of general courts and Corruption Crime courts. and qualitative analisis. Based on the research, it was found that differences in the procedural law of Corruption Crime courts compared to general court procedural law in the Indonesian criminal justice system were seen in the independence  of the Corruption Crime court institutions and the material that became the authority and the judicial process with the composition and members of the Panel of Judges consisting of career judges and ad hoc judges. division of duties for the presiding judge and its members, the period of time for the examination of the Corruption Crime and the evidence used, as well as their secret registrations which are also special in nature.